2015
DOI: 10.1161/hypertensionaha.115.05726
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Central PPAR-γ Attenuates Angiotensin II–Induced Hypertension

Abstract: Inflammation and renin-angiotensin system activity in the brain contribute to hypertension through effects on fluid intake, vasopressin release, and sympathetic nerve activity. We recently reported that activation of brain peroxisome proliferator-activated receptor (PPAR)-γ in heart failure rats reduced inflammation and renin-angiotensin system activity in the hypothalamic paraventricular nucleus and ameliorated the peripheral manifestations of heart failure. We hypothesized that activation of brain PPAR-γ mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 61 publications
2
22
0
Order By: Relevance
“…Several studies showed that the rostral ventrolateral medulla contains high concentrations of AT 1 receptors (Head, 1996) and is a major site of the sympathoexcitatory action of central AngII. AT 1 receptor expression was upregulated by AngII in this area and in the subfornical organ, the paraventricular hypothalamic nuclei, and the solitary tract nuclei (Yoshimura et al, 2000;Yu et al, 2015). Thus, elevated central AngII may act to upreglulate AT 1 receptors in the brainstem.…”
Section: Discussionmentioning
confidence: 85%
“…Several studies showed that the rostral ventrolateral medulla contains high concentrations of AT 1 receptors (Head, 1996) and is a major site of the sympathoexcitatory action of central AngII. AT 1 receptor expression was upregulated by AngII in this area and in the subfornical organ, the paraventricular hypothalamic nuclei, and the solitary tract nuclei (Yoshimura et al, 2000;Yu et al, 2015). Thus, elevated central AngII may act to upreglulate AT 1 receptors in the brainstem.…”
Section: Discussionmentioning
confidence: 85%
“…Like glutamate, TNFα activity in the PVN is implicated in blood pressure control. Increased TNFα levels in the PVN, originating from a microglial source (Shi et al, 2010), are associated with the increased local neural activity (Kang et al, 2008, Yu et al, 2015), as well as elevated systemic blood pressure (Sriramula et al, 2013, Dai et al, 2015, Dange et al, 2015) and sympathetic activity (Dange et al, 2015, Yu et al, 2015) that accompany experimental hypertension (Shi et al, 2010, Yu et al, 2015). In addition, acute PVN TNFα administration increases sympathetic activity and blood pressure (Bardgett et al, 2014, Shi et al, 2014), and inhibiting central TNFα has been shown to block forms of experimental hypertension (Song et al, 2014) including the increase in blood pressure occurring with AngII administration (Sriramula et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Within the PVN, TNFα transcription is induced by challenges such as immunological stress (Kakizaki et al, 1999, Masson et al, 2015a). In addition, increased TNFα levels in the PVN are associated with increased local neural activity (Kang et al, 2008, Yu et al, 2015), as well as elevated systemic blood pressure (Sriramula et al, 2013, Dai et al, 2015, Dange et al, 2015) and sympathetic activity (Dange et al, 2015, Yu et al, 2015). All of these physiological responses accompany preclinical models of hypertension including the elevated blood pressure induced by angiotensin II (AngII), a critical blood pressure regulating molecule (Shi et al, 2010, Yu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 On the other hand, the activation of brain PPARg in heart failure rats can reduce central inammation and brain renin-angiotensin system activity, ameliorating angiotensin II-induced hypertension in heart failure. 29,35 Thus, central PPARg may be the therapeutic target in treating hippocampus damage in myocardial infarction-induced HF. In present study, we found that PPARg was reduced in the hippocampus in rats with heart failure.…”
Section: Discussionmentioning
confidence: 99%